Hydrogen production in reactors: The influence of organic loading rate, inoculum and support material. (18th October 2019) - Vilela, Rogério; Saia, Flávia Talarico; Gregoracci, Gustavo Bueno; Duarte, Rubens; Andrade, Pedro; van der Zaan, Bas; Langenhoff, Alette; Damianovic, Márcia H.R. Z.
Abstract: Hydrogen production was evaluated in two thermophilic structured bed (USBR) reactors. USBR1was inoculated with auto-fermented sugarcane vinasse and low-density polyethylene cubes were used as support material. USBR2 was inoculated with anaerobic sludge from an up-flow anaerobic sludge blanket (UASB) reactor treating sugarcane vinasse, and polyurethane foam matrices was used as support material. The reactors were operated in parallel with sugar cane molasses at organic loading rate (OLR) from 30 to 120 g COD L −1 d −1 during 45 days. Hydrogen production was detected during the whole operational period, with maximum values of 1123 mL H2 d −1 L −1 and 2041 mL H2 d −1 L −1 for USBR1 and USBR2, respectively. The number of gene copies encoding for Fe - hydrogenase was higher in USBR2 for all OLR applied. DNA sequences related to Thermoanaerobacterium and Clostridium sensu stricto were predominant in USBR1. In USBR2, in addition to these microorganisms, Lactobacillus, Pseudomonas and Thermotuga, and sequences with low frequency of abundance (<5%) involved directly and indirectly in hydrogen production were also present. The taxonomical and functional more diverse inoculum of USBR2 was associated with a higher hydrogen production. Besides fermentation, an unknown metabolism was relevant in USBR2, revealing the importance of physiological characterization of the microbial community present. Highlights: Sugarcane molasses was suitable for thermophilic hydrogen production. Inocula, support material and OLR influenced hydrogen production. Thermoanaerobacterium, Clostridium sensu stricto and Thermotuga were selected.